Developing arts-based methods for exploring virtual reality technologies: A university–industry case study. (21st September 2021) - Gray, Stuart; Bevan, Chris; Cater, Kirsten; Gildersleve, Jo; Garland, Caroline; Langdon, Oliver
Abstract : page_246 other Collaborations between human–computer interaction (HCI) researchers and arts practitioners frequently centre on the development of creative content using novel – often emergent – technologies. Concurrently, many of the techniques that HCI researchers use in evaluative participant-based research have their roots in the arts – such as sketching, writing, artefact prototyping and role play. In this reflective paper, we describe a recent collaboration between a group of HCI researchers and dramatists from the immersive theatre organization Kilter, who worked together to design a series of audience-based interventions to explore the ethics of virtual reality (VR) technology. Through a process of knowledge exchange, the collaboration provided the researchers with new techniques to explore, ideate and communicate their work, and provided the dramatists with a solid academic grounding in order to produce an accurate yet provocative piece of theatrically based design fiction. We describe the formation of this partnership between academia and creative industry, document our journey together, and share the lasting impact it has had upon both parties.